The Role of SWOT Analysis in Improving HR Effectiveness and Employee Performance Case Study: CV 06 Production - Miranda Astari; Yusleli Herawati; Hadi Jauhari (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze the implementation of human resource management (HRM) and its impact on employee performance at CV. 06 Production, using a SWOT analysis as an evaluation tool. The research approach used was descriptive qualitative, with data collection methods including in-depth interviews, documentation, and direct observation of event implementation by the internal team. The results indicate that internal strengths such as team competence, effective communication, and prompt problem-solving significantly support employee performance. However, weaknesses in the organizational structure exist, such as the lack of a dedicated HR division and a nonstandardized performance appraisal system. The SWOT analysis indicates that employee performance development strategies can be improved through the establishment of an objective indicator-based evaluation system and the enhancement of transparent and continuous training. Therefore, improvements in HRM implementation will increase teamwork effectiveness in every event project undertaken by CV. 06 Production.